Enhancing Students’ Critical Thinking Skills Through Blended and Project-based Learning Approaches - Angraini, Syilvia; Joni, Erian (Universitas Jambi, Indonesia, 2024)
In the era of globalization and rapid information technology advancement, education must continuously adapt to prepare the younger generation with relevant skills. One crucial skill that needs to be instilled is critical thinking ability. This research investigates the influence of project-based learning through blended learning with Canva and Capcut media on enhancing necessary thinking skills. This research employs a quantitative approach through a quasi-experimental method. The research sample comprises students from classes A and B of one of junior high school in West Sumatera who enrolled in the Social Studies subject, where class A serves as the experimental group and class B as the control group. The research findings reveal that project-based and blended learning aided by Canva and Capcut media can enhance students' critical thinking skills.